1995
DOI: 10.1152/ajpheart.1995.269.1.h153
|View full text |Cite
|
Sign up to set email alerts
|

Baseline arterial pressure affects sympathoexcitatory responses to ventricular premature beats

Abstract: The seconds to minutes before sudden cardiac death are characterized by fluctuations of arterial pressure, cardiac rhythm, and probably sympathetic nerve activity. We explored the interrelations among these factors in seven patients undergoing clinical electrophysiological testing. We measured muscle sympathetic nerve activity (SNA) and arterial pressure responses to ventricular premature beats induced throughout the cardiac cycle under three conditions: 1) lowered arterial pressure and elevated SNA produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Furthermore, in these subjects the above-mentioned changes were followed by a transient diastolic BP increase and a concomitant transient suppression of spontaneous MSNA bursts. These findings are in line with the results of previous studies performed in both experimental animals 17 and humans, 1,18 in which a provoked PVC elicited, along with a diastolic BP reduction, a marked increase in cardiac, renal, and skeletal muscle sympathetic outflow, which was followed by a BP overshoot and a concomitant period of sympathetic silence. We can thus conclude that in healthy subjects, the sympathetic responses to provoked and unprovoked PVCs are qualitatively similar to each other, and thus, artificially induced PVCs represent a valid model for studying the hemodynamic and neural adjustments to spontaneously occurring arrhythmias of this type.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, in these subjects the above-mentioned changes were followed by a transient diastolic BP increase and a concomitant transient suppression of spontaneous MSNA bursts. These findings are in line with the results of previous studies performed in both experimental animals 17 and humans, 1,18 in which a provoked PVC elicited, along with a diastolic BP reduction, a marked increase in cardiac, renal, and skeletal muscle sympathetic outflow, which was followed by a BP overshoot and a concomitant period of sympathetic silence. We can thus conclude that in healthy subjects, the sympathetic responses to provoked and unprovoked PVCs are qualitatively similar to each other, and thus, artificially induced PVCs represent a valid model for studying the hemodynamic and neural adjustments to spontaneously occurring arrhythmias of this type.…”
Section: Discussionsupporting
confidence: 92%
“…[12][13][14][15][16] In the present study, we investigated the behavior of the changes in MSNA, as directly quantified by microneurography, that follow spontaneous unprovoked PVCs in healthy subjects and in patients with EH or CHF. Because evidence in animals and man 1,17,18 suggests that the sympathetic changes after provoked PVCs are related to (1) the blood pressure (BP) changes induced by PVCs, (2) their degree of prematurity (expressed by the coupling interval time), and (3) the level of the resting sympathetic tone, we further investigated in the 3 groups the relationships between the MSNA adjustments to spontaneous PVCs and the above-mentioned variables. …”
mentioning
confidence: 99%
“…The post-VPC drop of diastolic blood pressure initiates a surge of muscle sympathetic nerve activity, which is immediately followed by a period of sympathetic silence (27)(28)(29)(30)(31). The magnitude of this burst, which cannot be observed earlier than at the time of the first post-VPC beat, provokes noradrenaline release in perivascular sympathetic endings, leading to an increase of peripheral vascular resistance.…”
Section: Physiologic Background and Pathophysiology Of Hrtmentioning
confidence: 99%
“…Several studies indicated that a large multiunit MSNA burst occurred during premature ventricular contraction (PVC; Ando et al, 1997; Grassi et al, 2002) and atrial fibrillation (AF; Grassi et al, 2003; Wasmund et al, 2003) in HF patients. The low diastolic pressure induced by these arrhythmic conditions unloads arterial baroreceptors and evokes a larger and longer multiunit MSNA burst (Welch et al, 1989; Smith et al, 1995). However, only counting multiunit MSNA could cause the actual level of sympathetic nerve activity to be underestimated, because a large sympathetic activity burst could produce prolonged sympathetic inhibition.…”
Section: Assessment Of Muscle Sympathetic Nerve Activity During Irregmentioning
confidence: 99%